The Evolution of Virulence in Non-O157 Shiga Toxin-Producing Escherichia Coli - Coombes, Brian K.; Gilmour, Matthew W.; Goodman, Chelsey D. (Frontiers in Microbiology, 2011)
Shiga toxin-producing Escherichia coli (STEC) are zoonotic foodborne and waterborne pathogens that are a serious public health concern because they cause outbreaks and the potentially fatal hemolytic uremic syndrome (HUS). The most common STEC serotype associated with human disease is O157:H7, but there is a growing recognition of over one hundred non-O157 serotypes that also may result in human illness. Some of these non-O157 STEC strains cause outbreaks and severe disease such as HUS and hemorrhagic colitis, whereas others are associated with only mild diarrhea or with no human disease at all. The relative scarceness of whole genome sequence data for non-O157 STEC has limited the scientific discovery into the genetic basis of these differences in virulence. Uncovering the scope of genetic diversity and phylogeny of the non-O157 STEC through targeting sequencing of clinically relevant isolates will offer new biological insight to the pathogenic behavior of these emerging pathogens. These approaches would also enable molecular risk assessment strategies to rapidly identify and respond to emerging non-O157 STEC that pose a serious public health risk to humans.